Globalisation, the European Union and Turkey: rethinking the struggle over hegemony - Uzgoren, Elif (2012)
The research approaches Turkish membership question to the European Union as an open-ended struggle among social forces. It aims to address whether there is a hegemonic pro-membership perspective and if any, which social forces are supporting it. Is there any alternative contesting and resisting membership and neo-liberal restructuring? Can disadvantaged groups from globalisation form a united struggle, and if not, how can we account for the lack of an alternative? At the theoretical level, it dismisses mainstream integration theories as debate is mainly stuck to the dichotomy between membership or not (form of integration), that in return is a non-debate. It introduces Gramscian historical materialist framework that paves the way to account for socio-economic content and power relations underpinning ongoing integration process. The argument proceeds by delving into a debate on theoretical coordinates regarding hegemony in Gramscian analyses and the theory of discourse introduced by Laclau and Mouffe in the Hegemony and Socialist Strategy. Ultimately, it dismisses theory of discourse and conceives class struggle in relation to discipline of capital over society within social relations of production. The empirical data relies on semi-structured interviews conducted with capital and labour, political parties, state officials and women rights/feminist groups and human rights groups. Additionally, particular sectors, textile, automotive and agriculture are examined in parallel with Gramscian historical materialist coordinates on intra-class struggle.